The Role of Teachers in Implementing the Tolaki Dance Arts at SDN 02 Konda, South Konawe Regency - Apri Ayu Nandarestu; Chairan Zibar L. Parisu; Erwin Eka Saputra (Journal of Education and Learning Sciences, 2025)
This research aims to describe the role of teachers in implementing the Tolaki dance and identify supporting and inhibiting factors in its implementation at SDN 02 Konda, South Konawe Regency. This research used a qualitative approach with a descriptive research type and case study design. The research informants numbered 11 informants consisting of the principal, teachers, and students. Data was collected through interviews and documentation. Data analysis used the Miles and Huberman model, which included data reduction, data presentation, and drawing conclusions. The research results indicated that the teachers served as demonstrators, facilitators, mediators, and class managers in implementing the Tolaki dance. These roles were realized through providing examples of dance movements, utilizing media and learning facilities, introducing Tolaki culture to students, and providing direction during the learning process. The implementation of Tolaki dance has not been carried out evenly in all classes because some classes still focus on fine arts materials and have not integrated Tolaki dance in learning. Supporting factors included student enthusiasm, school support, availability of supporting facilities, and collaboration with external parties through Tolaki dance training activities. Meanwhile, inhibiting factors included the limited number of teachers capable of teaching Tolaki dance, limited supporting facilities, and uneven implementation of Tolaki dance across classes. This research concludes that teachers play a crucial role in the implementation of Tolaki dance at SDN 02 Konda, although its implementation still faces several obstacles that require support from various parties.